A liquid marble method for synthesizing large-sized carbon microspheres with controlled interior structures. (July 2021) - Xue, Nan; Cao, Jie; Zhang, Xiaoming; Li, Congming; Ettelaie, Rammile; Liu, Xian; Yang, Hengquan
Abstract: Millimeter-sized porous carbon spheres (MPCS) with both controllable interior architecture and high mechanical strength are highly desired for practical applications, but there is no efficient method to synthesize these materials. Here, we report a strategy to fabricate millimeter-sized porous carbon spheres by harnessing the liquid marble phenomenon. This strategy enables us to obtain a series of MPCS with tunable interior architectures, such as honeycombed MPCS, foam-like MPCS, cavity-containing MPCS and hollow MPCS, which add new members to carbon microsphere family. Crucially, the mechanical strength of MPCS reaches as high as 14.6 N, favoring its practical applications. Moreover, our protocol allows for nitrogen element and metal to be in situ incorporated within the body of MPCS, leading to an efficient catalyst for levulinic acid (LA) hydrogenation or benzene hydrogenation. Impressively, turnover numbers (TONs) of 113000 in the LA hydrogenation and 480 h of continuous benzene hydrogenation with TONs of 116000 are achieved, which highlights the potential in engineering applications of these novel microspheres. Graphical abstract: Image 1 Highlights: It is the first time that millimeter-sized porous carbon spheres are synthesized by harnessing the liquid marble phenomenon. Interior porous structure, particle size and mechanical strength can be tailored through regulating the synthesis conditions. The fundamental principles underpinning the formation of MPCS and the insights into the structural evaluation are revealed. The developed Ru/MPCS catalyst exhibited high activity in levulinic acid hydrogenation with the turnover numbers of 113000.